Pendidikan Karakter untuk Anak Usia Dini - Rika Devianti; Suci Lia Sari; Indra Bangsawan (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2020)
Early childhood (0-6 years old) at the golden age is easy to immitate and very receptive. Character education should thus be applied by educators and or parents as main educators in their life. Library research is used in this research by analyzing journals, books, printed and online documents, and relevant data. There are 4 methods and 12 strategy needed by educators and or parents in applying character education for early childhood. Sustainable education will develop character of children to adult, because it is influenced by not only genes but also environment like education.